Strategi Pembelajaran PAI Kurikulum Berbasis Cinta pada SMK Kesehatan Athalla Putra Palembang - Muhammad Arif Indra Budiman; Ahmad Zainuri; Arni Arni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic Religious Education plays a pivotal role in the formation of students’ character, particularly within the setting of vocational health education. In light of the introduction of the Love-Based Curriculum initiated by the Indonesian Ministry of Religious Affairs, there is a pressing need for instructional strategies that effectively integrate the values of love, compassion, tolerance, and empathy into PAI teaching. This study seeks to provide a comprehensive description and critical analysis of the love-oriented PAI learning model implemented at SMK Kesehatan Athalla Putra Palembang, while also examining the challenges encountered and the solutions undertaken in its execution. The research adopts a qualitative field study approach, with data collected through classroom observations, in-depth interviews with teachers and students, as well as document analysis. The findings indicate that several strategies have been employed, including interactive lectures, collaborative group discussions, socially oriented project-based learning, and the utilization of media designed to promote compassion. The successful implementation of the Love-Based Curriculum in this context is shaped by factors such as teacher competence, institutional support, and the adequacy of educational facilities. Nevertheless, a number of obstacles were identified, namely time constraints, limited professional training for teachers, and resistance to pedagogical change. Despite these challenges, the applied strategies proved to be effective in enhancing both student motivation and character development. Accordingly, it is recommended that the institution reinforce teacher professional development programs, establish a more structured syllabus, and institutionalize love-based values within both assessment practices and the broader school culture.